'Something's Not Right in Silverhöjd': Nordic Supernatural and Environmental and Species Justice in Jordskott. Issue 3 (3rd July 2022) - Kosonen, Heidi; Greenhill, Pauline
Abstract: In the Swedish/Finnish/British/Norwegian television series Jordskott (2015–17) child victims' mysterious disappearances signal that 'something's not right' in Silverhöjd, a Swedish town. Three detectives uncover a conflict between the locals who depend on a local industry and preternatural human-like but non-human forest creatures familiar from Nordic tradition and fairylore. Both humans and semi/non-humans are ambivalent, but what sets the latter apart is their implication in caring for nature, protecting it, and punishing those who harm it. We analyse this series' instantiation of a folkloristic popular green criminology, based in the idea that popular discourses' representations of crimes and harms may offer serious interventions into issues of environmental, ecological, and species justice. Our ecocritical analysis suggests that tradition offers material for reflection, but also for sociocultural intervention, as it is circulated to address the dependencies and hierarchical configurations between humans and other life-forms, and the many consequences of ecological and individual harm.